Fructose 1,6-Bisphosphatase 2 Plays a Crucial Role in the Induction and Maintenance of Long-Term Potentiation - Przemysław Duda (Cells, 2020)
Long-term potentiation (LTP) is a molecular basis of memory formation. Here, we demonstrate that LTP critically depends on fructose 1,6-bisphosphatase 2 (Fbp2)—a glyconeogenic enzyme and moonlighting protein protecting mitochondria against stress. We show that LTP induction regulates Fbp2 association with neuronal mitochondria and Camk2 and that the Fbp2–Camk2 interaction correlates with Camk2 autophosphorylation. Silencing of Fbp2 expression or simultaneous inhibition and tetramerization of the enzyme with a synthetic effector mimicking the action of physiological inhibitors (NAD+ and AMP) abolishes Camk2 autoactivation and blocks formation of the early phase of LTP and expression of the late phase LTP markers. Astrocyte-derived lactate reduces NAD+/NADH ratio in neurons and thus diminishes the pool of tetrameric and increases the fraction of dimeric Fbp2. We therefore hypothesize that this NAD+-level-dependent increase of the Fbp2 dimer/tetramer ratio might be a crucial mechanism in which astrocyte–neuron lactate shuttle stimulates LTP formation.